Desain Komunikasi Visual untuk Menunjang Penjualan Berbasis Bisnis Online bagi Pemula - Farhia, Yusaira (Bina Nusantara University, 2011)
Living in Jakarta, as one biggest business centre and largest target market, increases people awareness for doing entrepreneurship. However, for many business people with minimal capital, the choice is to run online business. Since internet as one familiar thing among society, the chance of online business isincreasing. Research method used is questionnaire randomly for 20 respondents, internet and literature study. One online shop will be easier and structured in designing concept. This research is about the importance of visual communication design in the appearance of online business. Visual communication design will produce something with quality and increase product value and sales from online shop. Through the application of simple design element, a good and quality online shop will be created so it could help and give benefit for large audience.